Experimental investigation on air-cooling type loop thermosyphon thermal characteristic with serpentine tube heat exchanger. (June 2022) - He, Yichuan; Hu, Chengzhi; Li, Hongyang; Hu, Xianfeng; Tang, Dawei
Highlights: Thermal characteristics in loop thermosyphon with serpentine tube heat exchanger are studied. Wide filling ratios of 10.4%∼99% and input heat flux of 16.7∼266.7 Wcm −2 are examined. Flow instability and transient response are studied. The serpentine tube condenser provides a small thermal resistance. Abstract: The loop thermosyphon, which has an excellent heat transfer performance, can effectively solve the problem of high heat flux heat transfer in outdoor high-power electronic equipment. In order to solve the problem of high heat flux heat transfer, the researchers focused on the new evaporator, but the impact of the condenser on the entire system cannot be ignored. This paper designed an air-cooling type loop thermosyphon with a condenser composed of a serpentine copper tube and corrugated aluminum fins. The experiment confirmed the serpentine tube condenser is a condenser with excellent performance. It can be used in conjunction with the loop thermosyphon to realize the 266.7 Wcm −2 heat flux transfer. Intriguingly, using a serpentine tube evaporator will bring about two kinds of flow instability, and the filling ratio is the key to restraining the flow instability. A high filling ratio is a suitable choice, which avoids flow instability and has a fast transient response. Moreover, the air temperature has little effect on the thermal resistance and the maximum temperature difference of the loop thermosyphon; therefore, this loop thermosyphon can be used in various weather conditions. However, extreme weather conditions (extremely high/ low temperature) may affect the performance of the loop thermosyphon. Consequently, the loop thermosyphon with serpentine finned tube condenser at an optimized high filling ratio is worthy of being employed in outdoor high-power electronic equipment.